Game theory approaches for autonomy - Dennis, Steven; Petry, Fred; Sofge, Donald (Frontiers in Physics, 2022)
Game theory offers techniques for applying autonomy in the field. In this mini-review, we define autonomy, and briefly overview game theory with a focus on Nash and Stackleberg equilibria and Social dilemma. We provide a discussion of successful projects using game theory approaches applied to several autonomous systems .